RESEARCH OF THE MAIN COMPONENTS OF INNOVATIVE CAPACITY OF THE INDUSTRIAL ENTERPRISE - M. Shtrikunova; I. Vrublevsky; I. Gurtskaiya (Вестник университета)
The available methodological base of research of innovative capacity of the industrial enterprise is developed, methods definitions and measurements of innovative potential are given. It allowed to offer approach to adoption of administrative decisions in the field of a choice of a certain type of innovations depending on the level of innovative capacity of the enterprise.